Histochemical and Immunohistochemical Investigation of Endocrine Tissue of Pancreas after Damage Caused by B-cytotoxic Chemicals and its Prevention by L-Hystidine - Meyramov, G.G.; Kohnert, K.-D.; Korchin, V.I.; Kartbaуeva G.T.; Shaybek, A.Zh.; Abdraimova, A.G.; Zhuzbaeva, G.O.; Dupont, O.-N.; Kovalenko, O.L.; Khlystova, L.V.; et al. (Fundamental and Experimental Biology, 2017)
Authors investigated a possibility of prevention developing of experimental diabetes in animals caused by group diabetogenic Zn-binding substances by preliminary injection of amino acid L-Hystidine contains the sulfhydril SH-groups in structure of molecule. It is established that intravenous administration of solution of 900-1000 mg/kg L-Hystidine to rabbits leads to the almostcomplete binding of ions of Zinc in B-cells of pancreas for 24 hours and prevent of formation in B-cells of a toxic complex Zinc-dithizon that is followed by prevention of developing of diabetes at 11 animals from 12. At the same time by comparative using of various histochemical research technics staining of tissue of pancreas it was shown that most sensitive for identification of insulin and Zinc in B-cells are fluorescent methods. The most qualitative results of assessment of features of gistotopography of insulin and Zinc in B-cells obtained by using of Aldehyde-fucshine method.